CytoLyt fixation significantly inhibits MIB1 immunoreactivity whereas alternative Ki‐67 clone 30‐9 is not susceptible to the inhibition: Critical diagnostic implications. Issue 10 (9th August 2019) - Buonocore, Darren J.; Konno, Fumiko; Jungbluth, Achim A.; Frosina, Denise; Fayad, Mariam; Edelweiss, Marcia; Lin, Oscar; Rekhtman, Natasha
Abstract : Background: The Ki‐67 proliferation marker has multiple diagnostic and prognostic applications. Although several clones to the Ki‐67 antigen are commercially available, the MIB1 clone is widely recommended in the surgical pathology literature for neuroendocrine tumors. In our cytopathology practice, we have encountered unexpectedly low MIB1 immunoreactivity in CytoLyt‐fixed cell blocks (CBs). The current study evaluated the impact of fixatives, CB processing, and immunocytochemical (ICC) procedures on Ki‐67 immunoreactivity. Methods: Test CBs were prepared from freshly resected tumors, and multiple variables in the MIB1 ICC procedure were tested, including CytoLyt versus formalin collection media, MIB1 versus other Ki‐67 clones including 30‐9, and other variables. MIB1 versus Ki‐67 30‐9 clones were tested in parallel on CytoLyt‐fixed CBs from clinical samples of small cell lung carcinoma (SCLC). Results: In the test CBs (n = 10), the mean MIB1 labeling index was 10% in CytoLyt versus 47% in formalin ( P = .0116), with a mean loss of reactivity in matched CBs of 37% (up to 70%). None of the procedure modifications tested in 223 individual ICC reactions recovered MIB1 reactivity in CytoLyt except for switching to the Ki‐67 30‐9 antibody. In CytoLyt‐fixed SCLC samples (n = 14), the Ki‐67 30‐9 antibody demonstrated expected ranges of reactivity (mean, 83%; range, 60%‐100%), whereas MIB1 demonstrated markedly inhibited labeling (mean, 60%; range, 10%‐95%) ( P = .0058). Conclusions: CytoLyt fixation substantially inhibits MIB1 immunoreactivity, whereas the Ki‐67 30‐9 clone is not susceptible to inhibition. Markedly discrepant MIB1 reactivity may present a pitfall in the diagnosis of SCLC and may lead to the incorrect prognostic stratification of other tumor types. For laboratories using CytoLyt, we recommend using the Ki‐67 30‐9 antibody rather than the MIB1 antibody. Abstract : CytoLyt fixation substantially inhibits MIB1 immunoreactivity and may present a diagnostic pitfall in certain tumors, especially small cell carcinoma. The Ki‐67 30‐9 clone demonstrates adequate performance and should be the clone of choice in laboratories using CytoLyt collection media.